Analisis Resepsi Penonton terhadap Hubungan Ibu dan Anak pada Film "Our Season" - Suwandi, Elsawati; Alamiyah, Syifa Syarifah (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
"Our Season" is a South Korean family fantasy drama film that presents the complexity of the emotional relationship between mother and child. This study aims to examine how the audience constructs the meaning of the mother-child relationship depicted in the film. With a qualitative approach and using Stuart Hall's reception analysis theory, this study explores various meanings from five informants. The results show that openness is understood as a form of selective honesty, while the mother-child relationship in the film is understood as a relationship full of wounds and openness is understood as the result of wounds of regret. Informants in the Dominant Hegemony position accept the film's message in its entirety and emphasize the importance of a mother's hierarchical values. Meanwhile, informants in the Negotiation position agree with some of the film's messages, but doubt its application in real life. Meanwhile, informants in the Opposition position reject the values conveyed by the film, considering it too biased towards children, and not highlighting parental responsibility enough. These findings demonstrate how personal experiences shape interpretations of family representations in the media, particularly in the context of emotional communication between mothers and children.